Estudos de variabilidade metabolômica de espécies de palma - Matos, Thiago Kelvin Brito (2016)
The prickly pear is a cultivation that has big importance on the Brazilian northeast semiarid area, which affects directly the economic success of this area. The prickly pear is mainly used as a forage plant, because this cactaceous is able to produce a great amount of green matter even in long rainless periods. However, the prickly pear is being attacked by a plague, especially the Carmine Cochineal. Although there are species that are resistant to this pathogen, the metabolomics base of this resistance is not known and studies that focus on establish a relation between the chemical composition and the resistance to the pathogen of the host are yet not explored. The metabolomics study of this research was done in four samples of prickly pear: giant pear (control), IPA pear, elephant ear pear e sweet pear. The study also proposes to compare the metabolites level in different cladodes from different prickly pear cultivars, in which each cultivar has a different level of resistance to the pathogen, by chromatographic analysis in an ultra-performance system coupled with a highresolution mass spectrometry (UPLC-QTOF-MSE). The MassLynx software, (Waters Corporation) was used to process the UPLC data. All possible molecular formulas were calculated. These analyses aim to confirm the relation between the detected substances with the prickly pear resistance to the Carmine Cochineal. It was possible to verify the occurrence of flavonoids from the isorhamnetins as the big differentiating group among the prickly pear species.